2006
DOI: 10.7863/jum.2006.25.9.1193
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Cardiac Twist by a Sonographically Based 2-Dimensional Strain Analysis Method

Abstract: The 2DSR program can be used to study twisting action of the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…In the present study, STI analysis showed that LV basal rotation improved significantly while apical rotation remained unchanged after ASD closure. As previous studies have consistently demonstrated, the normal LV performs a short-duration counterclockwise rotation that gradually changed into a more substantial clockwise rotation at the base [22][23][24][25]. However, our data showed a singularly reduced and delayed clockwise rotation following an abnormally enhanced and extended initial counterclockwise rotation at the basal level in patients with ASD.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In the present study, STI analysis showed that LV basal rotation improved significantly while apical rotation remained unchanged after ASD closure. As previous studies have consistently demonstrated, the normal LV performs a short-duration counterclockwise rotation that gradually changed into a more substantial clockwise rotation at the base [22][23][24][25]. However, our data showed a singularly reduced and delayed clockwise rotation following an abnormally enhanced and extended initial counterclockwise rotation at the basal level in patients with ASD.…”
Section: Discussioncontrasting
confidence: 43%
“…The recent development of 2-dimensional ultrasound speckle tracking imaging (STI) has allowed LV torsional deformation to be evaluated noninvasively in a variety of patient populations [15][16][17][18][19][20][21][22][23]. The accuracy of this novel technique has been validated with sonomicrometry and tagged magnetic resonance imaging (MRI) [24,25].…”
mentioning
confidence: 98%
“…Temporal alterations in this stable speckle patterns are identified as moving further apart or closer together, and a series of regional strain vectors are calculated as change in length/ initial length. Accordingly, for atrial longitudinal strain myocardial thickening was represented with a positive value, color-coded as red; myocardial thinning was represented with a negative value, color-coded as blue; and then these were superimposed to conventional 2D images [20,21]. The tracking process and conversion to Lagrangian strains was performed offline in a dedicated software (EchoPAC PC 2D strain -BT 0.5.2 -GE Healthcare).…”
Section: Left Atrial Non-doppler Two-dimensional Strain (2dse)mentioning
confidence: 99%
“…It is also time-consuming, technically demanding, and expensive. 7,19 These limitations make MRI less attractive as a method of routinely studying patients, and those with a pacemaker or an internal cardioverter-defibrillator cannot be studied at all by MRI. Compared to MRI, echocardiography is a widely available, relatively inexpensive, noninvasive imaging method that is being used effectively to study dynamic cardiac function.…”
Section: Left Ventricular Rotation and Clinical Implicationsmentioning
confidence: 99%
“…[4][5][6] Recently, efforts have focused on 2D speckle-tracking imaging (STI) to assess LVrot. [7][8][9] Several studies have shown that 2D STI gives equivalent results when compared to magnetic resonance imaging (MRI) or Doppler tissue imaging (DTI) for measuring LVrot. 9 However, because of the 3-dimensional (3D) nature of cardiac deformation, 2D STI based on 2D imaging may not be robust enough for LVrot measurement because of speckle decorrelation or the loss of some speckles due to elevational motion (ie, through-plane motion).…”
mentioning
confidence: 99%